On the issue of responsibility of officials for violation of the rights of entrepreneurs - Rakhmetollov, A.K.; Kizdarbekova, A.S.; Bekisheva, S.D.; Tyll, L.T. (Bulletin of the Karaganda University “Law Series”, 2020)
The article is devoted to analysis of the effectiveness of the response of officials of state bodies and organizations to violations of the rights of entrepreneurs, ensuring their protection. One of the key indicators for assessing the performance of officials is the appeal of business entities. The work focuses on the characteristic violations of the rights of entrepreneurs encountered in law enforcement practice, as well as on the problems of legislative regulation of the responsibility of perpetrators. Along with officials of various bodies and organizations, violations of the rights of entrepreneurs are allowed by the law enforcement officials. The provision of Article 32 of the Code of the Republic of Kazakhstan On Administrative Infractions, according to which the law enforcement officials for administrative offenses, committed in the performance of official duties, are liable in accordance with regulatory legal acts regulating the procedure for serving in the relevant authorities, requires appropriate attention. The work also concludes that at present there is a need to distinguish between the limits of administrative and criminal liability, to specify at the legislative level the categories as «Illegal interference in entrepreneurial activity», «Interfering with legal entrepreneurial activity», and «Corporate raiding».